2016
DOI: 10.1108/rsr-03-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

A survey of information literacy credit courses in US academic libraries

Abstract: Purpose There is a lack of data about information literacy (IL) credit courses in US academic libraries. This paper aims to provide a detailed snapshot of IL credit courses, including percentages of libraries that offer credit courses, the number of credits offered, the audience and how public institutions differ from private nonprofits and for-profits. Design/methodology/approach The authors surveyed a stratified random sample of libraries at higher education institutions across all categories from the Carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Among findings that report on the prevalence of common methods of IL such as instructor-requested, individual consultations and self-paced tutorials, the report also indicates that 19 percent of the responding institutions offer a credit-bearing IL course. 8 Margaret Burke in 2012 discusses credit-bearing IL, specifically, and surveyed ACRL's Information Literacy Instruction listserv followers (ILI-L) to solicit their reports of how credit-bearing classes are being delivered at their institutions. The survey's premise assumes that credit-bearing IL is being offered, so results report on practical aspects of this type of effort, including assessment efforts, course development and philosophy, adjunct use, and more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among findings that report on the prevalence of common methods of IL such as instructor-requested, individual consultations and self-paced tutorials, the report also indicates that 19 percent of the responding institutions offer a credit-bearing IL course. 8 Margaret Burke in 2012 discusses credit-bearing IL, specifically, and surveyed ACRL's Information Literacy Instruction listserv followers (ILI-L) to solicit their reports of how credit-bearing classes are being delivered at their institutions. The survey's premise assumes that credit-bearing IL is being offered, so results report on practical aspects of this type of effort, including assessment efforts, course development and philosophy, adjunct use, and more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent survey by Cohen et al (2016) of US institutions of higher education found that only 19% of schools offer information literacy credit courses taught by librarians, and of these courses only 24% were more than two credit hours. A 2014 survey by the Canadian Association of University Teachers found that of the universities surveyed, 16% had academic librarians teaching Library credit courses as part of their regular workload.…”
Section: Literature Reviewmentioning
confidence: 99%
“…52 And it should be mentioned that teaching for-credit courses carries many assumptions other than university buy-in, not the least of which are adequate teacher training and ongoing support. The viability of this suggestion, then, relies on institutional climate and other significant educational factors.…”
mentioning
confidence: 99%